Comprehensive analysis of human protein N-termini enables assessment of various protein forms - Yeom, Jeonghun; Ju, Shinyeong; Choi, YunJin; Paek, Eunok; Lee, Cheolju (NATURE PUBLISHING GROUP, 2017)
Various forms of protein (proteoforms) are generated by genetic variations, alternative splicing, alternative translation initiation, co- or post-translational modification and proteolysis. Different proteoforms are in part discovered by characterizing their N-terminal sequences. Here, we introduce an N-terminal-peptide-enrichment method, Nrich. Filter-aided negative selection formed the basis for the use of two N-blocking reagents and two endoproteases in this method. We identified 6,525 acetylated (or partially acetylated) and 6,570 free protein N-termini arising from 5,727 proteins in HEK293T human cells. The protein N-termini included translation initiation sites annotated in the UniProtKB database, putative alternative translational initiation sites, and N-terminal sites exposed after signal/transit/propeptide removal or unknown processing, revealing various proteoforms in cells. In addition, 46 novel protein N-termini were identified in 5' untranslated region (UTR) sequence with pseudo start codons. Our data showing the observation of N-terminal sequences of mature proteins constitutes a useful resource that may provide information for a better understanding of various proteoforms in cells.
Keywords: ALTERNATIVE TRANSLATION INITIATION; MS-GF PLUS; DATABASE; PROTEOMICS; PEPTIDES; ACETYLTRANSFERASES; IDENTIFICATION; SEARCH; ACETYLATION; INSIGHTS